MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA(K3) PADA KARYAWAN LAUNDRY DEPARTMENT HOTEL ROCKY PLAZA PADANG - Morisa, Febby Erzam; Kasmita, Kasmita; Pramudia, Heru (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aims to determine the development of management safetyand healthy activity at staff laundry department Hotel Rocky Plaza Padang. Thisresearch consists of four indicators of management safety and healthy activity are job area, work use equipment, bright arrange, self work protection. This researchwas descriptive with qualitative data. Data was collected by using interviews,observations, and documentations in volving informations using purposivesampling. Management safety and healthy activity at laundry department staffHptel Rocky Plaza Padang are: 1) Presence program complete work useequipments of staff laundry department, 2) Bright organizing arrange for staffwith works, 3) offer directing for staff related with be needed safety and healthyactivity staff laundry department, 4) Controlling with control and frequentconsider related safety and healthy activity staff laundry department about whatmust kind and frequent consider, 5) Do evaluation with ptoportion and efectifmeasure in use achieve efforts business purpose. Conclution this research are atlaundry department Hotel Rocky Plaza Padangat the moment already be resent ofplanning but doesn’t yet for manage safety and healthy until management safetyand healthy can’t condition in the same manner as surely.Keywords: Management, safety and healthy activity, and laundry department